Seven databases in seven weeks : a guide to modern databases and the NoSQL movement - Redmond, Eric (Pragmatic programmers., 2012)
Redis, Neo4J, Couch, Mongo, HBase, Riak, and Postgres: with each database, you'll tackle a real-world data problem that highlights the concepts and features that make it shine. You'll explore the five data models employed by these databases: relational, key/value, columnar, document, and graph. See which kinds of problems are best suited to each, and when to use them. You'll learn how MongoDB and CouchDB -- both document oriented datastores that harness the power of JavaScript -- are strikingly different. Learn about the Dynamo heritage at the heart of Riak and Cassandra. Understand MapReduce and how to use it to solve Big Data problems. Build clusters of servers using scalable services like Amazon's Elastic Compute Cloud (EC2). Understand the tradeoffs between consistency and availability, and when you can use them to your advantage. Use multiple databases in concert to create a platform that's more than the sum of its parts, or find one that meets all your needs at once. Seven Databases in Seven Weeks will give you a broad understanding of the databases, their strengths and weaknesses, and how to choose the ones that fit your needs. You'll need a *nix shell (Mac OSX or Linux preferred, Windows users will need Cygwin), and Java 6 (or greater) and Ruby 1.8.7 (or greater). Each chapter will list the downloads required for that database.-- Publisher.